Production of Polyclonal Antibodies for Detection of Papaya ringspot virus (PRSV) in Ivy Gourd (Coccinia grandis (L.) - Noochoo, Sukanya; Sritongchai, Wanpen; Chowpongpang, Srimek (Agriculture and Natural Resources, 2015)
The coat protein (CP) gene from the Papaya ringspot virus (PRSV) strain Chiang Mai 1 (PRSV-CP) was cloned and expressed in Escherichic coli and purified using nickel-nitrilotriacetic acid agarose resin. The recombinant coat protein was used as an antigen to produce polyclonal antibodies for detection of PRSV in ivy gourd. The antibodies were able to detect the recombinant protein and PRSVinfected plant samples. Specificity of the antibodies to PRSV was compared with indirect enzyme-linked immunosorbent assay (ELISA), dot-blot immunobinding assay (DIBA) and tissue blot immunoassay (TBIA). It was found that the antibodies were highly specific and could be used to detect the presence of virus in different parts of ivy gourd. The antibodies were used to detect PRSV infection in ivy gourd using indirect ELISA and DIBA on 211 samples collected from papaya orchards. It was shown that 107 samples (50.71%) were infected by PRSV. In this study, results from germination testing on 195 seedlings from the infected ivy gourd seeds implied that PRSV was not seed transmitted. Furthermore, the results from TIBA revealed that PRSV spread to all parts of the ivy gourd (leaf, flower, flower stalk, stem and root, as well as tendril) even though some of the infected parts did not show any viral symptoms.